Christian friendship in the fourth century - White, Carolinne (Cambridge Cambridge University press, 1992)
Friendship was a quality valued highly in ancient Greece and Rome, and was also regarded as highly significant in nascent Christianity. Carolinne White's aim in this study is to describe and compare the ideas about friendship developed by the Christians whose culture was in many ways dependent upon its pagan background, and thus to develop a coherent picture of how the concept of friendship was understood in the fourth century. The Christian writers discussed are considered against the background of their personal lives and their relations with one another. All of the writers considered had a profound influence on later ages as well as on their own period, which means that the survey provided should be of wide interest both to ancient historians and theologians. [publisher's description]
Keywords: Friendship -- Religious aspects -- Christianity -- History of doctrines -- Early church, ca. 30-600; #GOSA:II.P.Alg.M; #GOSA:II.P.AU.3